Study of serum homocysteine level in cases of non-diabetic ischemic stroke - Murmu, Malati; K. P., Karun Mahesh; Dash, Sanjay; Singh, Lagendra Kumar; Kar, Ayaskanta; Mishra, Pravin Kumar (International Journal of Research in Medical Sciences, 2018)
Background: Aim of the study was to measure serum homocysteine levels in non-diabetic ischemic stroke and to co-relate its significance with other risk factors of ischemic stroke. It was a case control study. Methods: The study was done in the Department of Medicine, VSS.I.M.S.A.R, Burla, Odisha. 42 patients of non-diabetic ischemic and 42 age and sex matched controls were included in the study. Adults above the age of 18 years who were non-diabetic presenting with first-ever ischemic stroke, confirmed by CT scan of brain were included. Diabetic patients, haemorrhagic stroke, suspected embolic stroke, patients on vitamin supplementations, chronic usage of phenytoin were excluded. Routine investigations, fasting serum lipid profile and serum homocysteine levels were done. Results: Mean serum homocysteine level in ischemic stroke patients were found to be much higher (25.83 micro mol/L) in comparison to control group (9.77 micro mol/L) which is statistically significant. Mean serum homocysteine levels were found to be higher in patients with age group of more than 60 years, male sex, sedentary lifestyle, vegetarian diet, hypertensive patients and patient with normal fasting lipid profile. Statistical analysis for significance of difference was done using Chi-Square test with Yate’s correction. Conclusions: A statistically significant correlation was found between all the studied risk factors among non-diabetic patients and serum homocysteine levels. Estimation of serum homocysteine is advisable in all cases of non-diabetic ischemic strokes to know the prognosis.